GAMBARAN PELAKSANAAN KEGIATAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) BPJS KESEHATAN DI PUSKESMAS SIAK HULU III - Deovia, Wieke Serly; Sabrian, Febriana; Amir, Yufitriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
One of the efforts to improve the health status of the community and the success of social health insurance program is the participation in BPJSâ Chronic Disease Management Program (Prolanis) which focusing on promotive and preventive health service. This study aimed to identify the description of BPJS âChronic Disease Management Program (Prolanis) implementation in Siak Hulu III Community Health Center. The design of this study was descriptive. The samples were 30 respondents that were taken by saturated sampling technique. The measuring instrument was a questionnaire that has been tested for validity and reliability. The data was analyzed by univariate analysis to identify the frequency distribution. The results of the study showed that the description of prolanis implementation who all of respondents chose the yes answer about 30 respondents (100,0%) for medical consultation program at the first question about the chance for consultation, the second question about disease explanation, and the third question about the health workers who listen the disease complain, while for home visit activities program at the first question about giving the self healthy education and the second question about the environment health education, and for club activities program at the first question about giving of club activities facility, and for monitoring health status activities program at the first question about giving a chance to re-control and the second questions about giving a chance to observation of disease. It is expected that the results of this study could be used to improve the implementation of Prolanis BPJS program. Keywords : Community health center, health of BPJS, Prolanis